2019
DOI: 10.3390/ijms21010139
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Platelets in Patient’s Blood Influences the Mechanical and Morphological Properties of PRP-Clot and Lysophosphatidic Acid Quantity in PRP

Abstract: The objectives of this study were to compare platelet-rich plasma (PRP) from patients with different concentrations of platelets and to assess the influence of these PRP preparations on human osteoblast (hOB) activity. In the literature, growth factors released by activated platelets have been considered responsible for the active role of PRP on bone regeneration but no specific role has been attributed to lysophosphatidic acid (LPA) as a possible effector of biological responses. In this study, patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…This study highlights usage of tissue speci c requirements parameters to de ne quality of the PRP. This is in line with other musculoskeletal in vitro studies which have highlighted the effect of speci c platelet derived factors on the osteogenic potential of stem cell lines [11,13,17]. A study involving 15 subjects by Bernardi et al, [14] also highlights the fact that freeze-thawing technique for PRP can damage platelet membranes and may potentially affect the quality of PRP, especially in terms of slow and sustained release of factors in vivo.…”
Section: Outcome Measurementssupporting
confidence: 78%
See 2 more Smart Citations
“…This study highlights usage of tissue speci c requirements parameters to de ne quality of the PRP. This is in line with other musculoskeletal in vitro studies which have highlighted the effect of speci c platelet derived factors on the osteogenic potential of stem cell lines [11,13,17]. A study involving 15 subjects by Bernardi et al, [14] also highlights the fact that freeze-thawing technique for PRP can damage platelet membranes and may potentially affect the quality of PRP, especially in terms of slow and sustained release of factors in vivo.…”
Section: Outcome Measurementssupporting
confidence: 78%
“…In vitro studies. Studies have measured platelet derived factors in PRP and were able to demonstrate speci c pro-osteogenic gene activation in MSC derived commercial human cell lines [11,13,17] and umbilical cord derived human autologous MSC cell lines [6]. The product was characterized in terms of platelet yield and growth factors, proliferation of the MSC's in cell lines, and activation of speci c genes was noted to measure the e cacy of the product.…”
Section: Outcome Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Musculoskeletal system-based studies have demonstrated safety and efficacy of PRP in human studies [ 1 , 17 ]. We are now looking at the 4th generation approach where it is possible to design methods (using engineering techniques) to maintain slow and sustained release of platelet derived factors in vivo [ 13 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…, to albumin), and have dynamic biosynthesis and release (e.g. , with platelet degranulation [ 35 , 36 ]). As a result, LPA-targeting antibodies face the difficult task of removing actively and continuously produced LPA within not only signaling pools but also larger pools of structural membranes, vesicles, and other contributing compartments (e.g.…”
Section: Discussionmentioning
confidence: 99%